DIPG-44. MOLECULAR AND CHROMOSOMAL CHARACTERIZATION OF A UNIQUE SERIES OF DIFFUSE MIDLINE GLIOMAS IN CHILDREN AND YOUNG ADULTS. Issue 2 (22nd June 2018) - Dufour, Charlotte; Vasseur, Romain; Perbet, Romain; Leblond, Pierre; Vinchon, Matthieu; Reyns, Nicolas; Touzet, Gustavo; Maurage, Claude-Alain; Fabienne, Escande; Florence, Renaud
Abstract: Diffuse midline gliomas and especially diffuse intrinsic pontine gliomas are aggressive tumors with poor prognosis and no effective treatment. The identification of histone H3.3 mutations has been a large advance by defining groups with different prognoses. However, molecular and chromosomal landscape of these tumors needs to be further explored to identify key events of oncogenesis. We provide here a unique series of 55 diffuse midline gliomas with pre-treatment samples for each patient (frozen and/or FFPE samples). We performed CGH-array and next-generation sequencing, using a wide panel of genes involved in chromatin remodeling. Different immunohistochemical markers were tested. Survival and clinical data were also available. With molecular results, we reclassified every tumor according to WHO classification 2016. Within histone H3 mutant subgroup (74% of all the samples), 80% harbored a K27M H3.3 mutation and 20% a K27M H3.1 mutation. We identified additional somatic mutations in TP53 (55%), ACVR1 (20%) and PIK3CA (13%) and rarer mutations in BRAF, EGFR, PDGFRA, PPM1D, MED12, KIT, MET, ARID1B, CHEK2, FGFR1 and PIK3R1. Recurrent chromosomal alterations such as gain of 1q and 2, loss of 5q, 10q, 13, 14, 16q and 17p and amplification of PDGFRA were also identified. These data were correlated together and associated with survival in order to define different molecular subgroups. To conclude, these results allowed us to define more precisely the genomic landscape of these tumors and to identify recurrent molecular and chromosomal alterations, correlated to survival and relevant to be therapeutic targets.